Breaking up with my idol: A qualitative study of the psychological adaptation process of renouncing fanship - He, Yiqing; Sun, Ying (Frontiers in Psychology, 2022)
Introduction: This study aimed to explore the psychological adaptation process of renouncing fanship due to para-loveshock in the context of fandom culture. Methods We adopted netnography to explore social media platforms used by fans in China (Weibo, WeChat, and Douban) as research fields for 3 years. Results (1) The process of “breaking up with” or renouncing an idol can be divided into three phases: the resistance phase with acute stress, the negotiation phase with bargaining, and the recovery phase with attachment reconstruction. In the resistance phase, fans displayed acute stress responses due to loveshock in psychological, physical, and behavioral aspects. In the negotiation phase, fans faced four barriers to renouncement: cognitive dissonance, emotional attachment, behavioral dependence, and social threat. They bargained within the three types of cognitive framework before deciding to “leave” or “re-follow” their idol. In the recovery phase, fans adopted two types of strategies to promote recovery: healing the past and facing the future. Healing the past involved public outcry, sharing their breakup plans, cognitive reconstruction, and seeking closure to the fan role. Facing the future involved switching environments, seeking new interests, and inhibiting the re-intrusion of trauma cues. (2) Internal factors affecting the psychological adaptation process of renouncement include the level of initiative, attribution styles, experience, attachment status and core belief systems, and alternative lifestyles; external factors include social support, peer pressure from the fan community, life stressors, and types and impact of traumatic events. (3) Based on the two dimensions of orientation and commitment, fans were classified into four types: short-term rational, short-term passionate, bounded loyal, and unconditionally loyal, corresponding to non-traumatic, stressful, accumulated, and traumatic breakup processes, respectively. (4) The post-renouncement growth of fans mainly manifested in the development of mental modes, coping skills toward trauma, emotional adaptation experience, and behavior patterns. Implications This investigation of the recovery process from para-loveshock after renouncement of fanship can provide theoretical and practical insights into the development of psychological resilience for fans, reduction of the psychological distress and negative outcomes, and public governance on social media platform and cyber pop culture industry.